2010
DOI: 10.1111/j.1750-3841.2010.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Fish Oil by Spray Granulation and Fluid Bed Film Coating

Abstract: The stability of microencapsulated fish oil prepared with 2 production processes, spray granulation (SG) and SG followed by film coating (SG-FC) using a fluid bed equipment, was investigated. In the 1st process, 3 types of fish oil used were based on the ratios of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (10/50, 33/22, and 18/12). Each type was emulsified with soluble soybean polysaccharide (SSPS) and maltodextrin to produce 25% oil powders. In the 2nd process, 15% film coating of hydroxyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 72 publications
(83 reference statements)
1
24
0
7
Order By: Relevance
“…The image showed the microcapsules of SFD powders had spherical shape and porous surface structure. From Figures 5(b), 5(c), and 5(d), it was found that the microstructure of SD was similar to that of SFD with spherical shape structure but had smooth surface and occurrence of dents and cracks was less, which was similar to the spray granulation (SG) powder done by Anwar et al [32]. Aghbashlo et al [34] reported that the microcapsules produced by SD were almost spherical in shape and had a slightly smooth surface without any particle expansion, which was consistent with the results of this study.…”
Section: Scanning Electron Microscopysupporting
confidence: 69%
See 2 more Smart Citations
“…The image showed the microcapsules of SFD powders had spherical shape and porous surface structure. From Figures 5(b), 5(c), and 5(d), it was found that the microstructure of SD was similar to that of SFD with spherical shape structure but had smooth surface and occurrence of dents and cracks was less, which was similar to the spray granulation (SG) powder done by Anwar et al [32]. Aghbashlo et al [34] reported that the microcapsules produced by SD were almost spherical in shape and had a slightly smooth surface without any particle expansion, which was consistent with the results of this study.…”
Section: Scanning Electron Microscopysupporting
confidence: 69%
“…Microcapsule's microstructure and morphology are important to determine their stability, functionality, and flowability [32]. Figure 5 shows the scanning electron microscopy (SEM) images of fish oil microcapsules obtained by different drying methods (SD, FD, and SFD) in order to investigate the surface morphology and microstructure.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been purposed for microcapsule's production [13][14][15][16][17][18][19][20][21][22], in order to be adapted to different types of core and shell materials, as well as, to generate particles with various sizes, shell thickness and permeability, thus adjusting the release rate of the active principle. Generally these techniques can be divided into two major categories, namely chemical and physical methods; the latter one can be subdivided into physicochemical and physicomechanical techniques [6].…”
Section: Microencapsulation Methodsmentioning
confidence: 99%
“…Both maltodextrin and gum Arabic may be applied as the coating material. Gum Arabic is an effective carrier because of its high solubility in water, low solution viscosity and ability to form a protective fi lm around the particles of the dispersed phase of the emulsion [Dickinson et al, 1989 Arabic and constitutes an effective anti-oxygen barrier, but on the other hand it has poor emulsifying ability [Anwar et al, 2010]. Thus gum Arabic combined with maltodextrin may be a perfect matrix to protect β-carotene during spray--dried microencapsulation process.…”
Section: Introductionmentioning
confidence: 99%